Mathematical modeling of the spatial distribution of minerals using the interlinatsii - Бешанова, Антоніна Сергіївна (Technology audit and production reserves, 2012)
The article is devoted to the development of the methods of mathematical modeling the spatial distribution of minerals using data on the distribution of wells using the method interlineation function